Validity and reliability of evaluation instrument on Islamic education teachers’ training based on I-Cvi and Efa - Sapie Sabilan; Mohd Isa Hamzah; Ab. Halim Tamuri; Suhana Mohamed Lip (Penerbit Universiti Kebangsaan Malaysia, 2020)
This research aims to obtain validity and reliability of several research items in the teachers’ training evaluation intstrument for teachers in Sekolah Rendah Agama (SRA) JAIS, trained under the Intergrated Holistic Education System program (IHES).This instrument had been tested for validity and reliability using the Content Validity Index (I-CVI) and Exploratory Factor Analysis (EFA). A total of 122 JAIS Islamic Education teachers from Hulu Langat and Sepang district were selected as respondents in the pilot study.The face validity and content instrument were evaluated by ten field experts and I-CVI was used to determine the reliability score. The result of the value of item Content Validity Index (S-CVI) showed a high score for both constructs with 0.99 and 0.98 value. Four factors for teachers’attitude construct and three factors for teachers’ performance construct were developed through the use of EFA. Meanwhile an anti image showed the value of coefficient correlation exceeded 0.5 value ,which was between 0.77 to 0.92. Furthermore, the Eigen value was bigger than 1. While the item correlation value of the overall score (item-to-total correlation) exceeded 0.30 in between 0.38 to 0.77. Both constructs showed internal consistency values (Cronbach’s Alpha) of 0.90 and 0.94 , which values fell under acceptable range. All items showed load factor values exceeding 0.5.The overall items for this research consisted of 38 items for two research constructs. The conclusion from the EFA result showed that the teachers’ training evaluation instrument for JAIS Islamic Education teachers on the aspects of attitude and teachers’ performance has fulfilled the validity and reliability criteria.